3D transcranial ultrasound localization microscopy in awake mice: protocol and open-source pipeline - Georges Chabouh; Louise Denis; Myriam Abioui-Mourgues; Jean-Baptiste Deloges; Jacques Battaglia; Arthur Chavignon; Baptiste Heiles; Basile Pradier; Sylvain Bodard; Denis Vivien; Cyrille Orset; Olivier Couture (Communications Engineering)
Abstract We present an open-source code for 3D super-resolution ultrasound imaging. Open-3DULM was applied to transcranial imaging in habituated awake mice. Comparative analysis reveals that isoflurane anesthesia induces significant vasodilation and increased cerebral blood flow (CBF) in veins, while only a subset of arteries exhibits these effects compared to the awake state. This method could serve as a reference for developing new types of 3D vascular quantifications, particularly emphasizing the importance of awake and 3D imaging for accurate cerebral blood flow measurement in neuroscience research.